Calcio-Herbal Medicine Divya-Swasari-Vati Ameliorates SARS-CoV-2 Spike Protein-Induced Pathological Features and Inflammation in Humanized Zebrafish Model by Moderating IL-6 and TNF-α Cytokines - Balkrishna A; Verma S; Solleti SK; Khandrika L; Varshney A (Dove Medical Press, 2020)
Acharya Balkrishna,1,2 Sudeep Verma,1 Siva Kumar Solleti,1 Lakshmipathi Khandrika,1 Anurag Varshney1,2 1Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, Uttarakhand 249 405, India; 2Department of Allied and Applied Sciences, University of Patanjali, Haridwar, Uttarakhand 249 405, IndiaCorrespondence: Anurag Varshney Tel +91-1334-244107, Ext: 7458Email anurag@prft.co.inPurpose: Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection has grown into a pandemic and without a specific cure, disease management is the need of the hour through symptomatic interventions. Studies with severe acute respiratory syndrome-coronavirus (SARS-CoV) have highlighted the role of herbal medicines either in combination with antiviral drugs or by themselves in curtailing the severity of infection and associated inflammation. Divya-Swasari-Vati is an Indian ayurvedic formulation used in the treatment of chronic cough and lung inflammation, which is one of the first symptoms of SARS-CoV-2 infections.Methods: In this study, we used a A549 cell xenotransplant in the swim bladder of zebrafish and modeled the SARS-CoV-2 infection by injecting the fish with a recombinant spike protein. The different groups were given normal feed or feed mixed with either dexamethasone (as the control drug) or Divya-Swasari-Vati. The changes in behavioral fever, infiltration of pro-inflammatory cells in the swim bladder, degeneration or presence of necrotic cells in the kidney, and gene expression of pro-inflammatory cytokines were studied to determine the rescue of the diseased phenotype.Results: Challenge with the spike protein caused changes in the swim bladder cytology with infiltrating pro-inflammatory cells, skin hemorrhage, and increase in behavioral fever. This was also accompanied by increased mortality of the disease control fish. Treatment with Divya-Swasari-Vati reversed most of the disease symptoms including damage to the kidney glomerulocytes, and complete reversal of behavioral fever. Dexamethasone, used as a comparator, was only able to partly rescue the behavioral fever phenotype. Divya-Swasari-Vati also suppressed the pro-inflammatory cytokines, IL-6 and TNF-α, levels in a dose-dependent manner, under in vivo and in vitro conditions.Conclusion: The study showed that the A549 xenotransplanted zebrafish injected with the recombinant spike protein of SARS-CoV-2 is an efficient model for the disease; and treatment with Divya-Swasari-Vati medicine rescued most of the inflammatory damage caused by the viral spike protein while increasing survival of the experimental fish.Keywords: zebrafish, A549 xenotransplant, SARS-CoV-2 infection model, herbal medicines, ayurveda, Divya-Swasari-Vati, behavioral fever, cytokine profile